A Granger Causality Test (GCT) Approach to Exchange Rate Volatility on Prices of Selected Construction Materials in North-Central Nigeria - Abdulhaqq Muhammed; Chinedu Chimdi Adindu (International Journal of Economics Development Research (IJEDR), 2023)
The importance of construction materials to the Nigeria’s construction industry sub-sector cannot be overemphasized considering its monumental contribution to national infrastructure development, employment generation, and gross domestic product (GDP), to mention but a few. Unfortunately, there has been a continual upward surge in the prices of construction materials and its attendant effects on the volume of construction output owing to price vagaries. This study applied Granger Causality Test (GCT) to investigate the effect of Exchange Rate Volatility (ERV) on selected construction material prices for projects embarked upon within the North-Central geopolitical region of Nigeria. The data employed Exchange Rate Volatility (ERV) trend, and Average Price Trends (APT) of Cement, Block, Tile and Reinforcement for the period between 2011Q1 and 2020Q4. The results show p-values of 1.006e-05, 1.006e-05, 0.000668 and 1.006e-05 respectively  for Cement, Blocks, Tile and Reinforcement. Thus, implying that ERV do not granger-cause the selected construction material variable factors, which are Cement, Block, Tile and Reinforcement prices. The study concludes that exchange rate votality has a negative consequence on each of the selected construction materials with a unidrectional impact and same not happening in reverse. The study recommends the implementation  of requisite fiscal policies including reduction in the usage of other currencies other than the Naira to transact within Nigeria, stoppage of the use of US Dollars as an intermediary for international currency exchanges and an increase  in the  production capacity of local construction materials.